Status of the technologies for the production of the Cherenkov Telescope Array (CTA) mirrors - Pareschi, G. (2013)
The Cherenkov Telescope Array (CTA) is the next generation very high-energy gamma-ray observatory, with at least 10 times higher sensitivity than current instruments. CTA will comprise several tens of Imaging Atmospheric Cherenkov Telescopes (IACTs) operated in array-mode and divided into three size classes: large, medium and small telescopes. The total reflective surface could be up to 10,000 m2 requiring unprecedented technological efforts. The properties of the reflector directly influence the telescope performance and thus constitute a fundamental ingredient to improve and maintain the sensitivity. The R&D status of lightweight, reliable and cost-effective mirror facets for the CTA telescope reflectors for the different classes of telescopes is reviewed in this paper.